Kuat Tekan dan Kuat Tarik Belah Beton SCC dengan Campuran Kawat Baja - Madi Hermadi; Athaya Zhafirah; Chairul Insan (Institut Teknologi Garut, 2024)
Experimental innovations on concrete have been carried out by researchers, both chemical and physical, with the aim of improving the quality of concrete. One of the additional material options used that is physical is steel wire. The aim of adding steel wire is to optimize the quality of the concrete, both tensile and compressive strength. The method used in the following research is experimental by adding steel wire to the SCC concrete mixture with variations of 4%, 6% and 8%. As for the addition of chemical substances, the superplasticizer admixture aims to make it easier for SCC concrete to reach slump values. Based on the results of the split tensile and compressive strength tests of concrete after 28 days of age, it was found that the maximum compression test score was SCC concrete with a mixture of 8% steel wire with a compressive strength value of 20.36 MPa. Meanwhile, the maximum split tensile strength test results for SCC concrete were in concrete mixed with 8% steel wire with a split tensile strength value of 3.36 MPa.